IDENTIFICATION OF FUNCTIONS IN HARDY SPACE ON A HALF-STRIP DOMAIN - Dilnyi, V. M.; Pasternak, A. A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
This paper explores a signal identification problem using a convolution. We identify the signal with some function belonging to the Hardy space in a domain outside the half-strip. For this, we use a test function belonging to the Hardy space in the half-strip. Signals generated by point singularities and singularities generated by a segment are considered. The exponential test functions are chosen. For some cases, the exact solutions are found, for others, a convolution is found, and the possibility of finding the desired signal is analyzed.